2020
DOI: 10.1371/journal.pone.0228541
|View full text |Cite
|
Sign up to set email alerts
|

Anodal tDCS over the right parietal but not frontal cortex enhances the ability to overcome task set inhibition during task switching

Abstract: Switching between tasks requires individuals to inhibit mental representations of the previous task demands and to activate representations of the new task demands. The inhibition of the executed task remains active for a while so that when the inhibited task set must be reactivated shortly after, the need to overcome residual task set inhibition leads to behavioral costs. In a sham-controlled balanced-order within-subjects experimental design we investigated whether applying right anodal/left cathodal transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…The findings of Sdoia et al (2020) were obviously different from that of Dreher and Berman (2002) . The discrepancy of the conclusion could be due to the methodological differences, such as stimuli and experimental procedure between these two studies ( Sdoia et al, 2020 ).…”
Section: Brain Areas Associated With Bimentioning
confidence: 63%
See 3 more Smart Citations
“…The findings of Sdoia et al (2020) were obviously different from that of Dreher and Berman (2002) . The discrepancy of the conclusion could be due to the methodological differences, such as stimuli and experimental procedure between these two studies ( Sdoia et al, 2020 ).…”
Section: Brain Areas Associated With Bimentioning
confidence: 63%
“…While this expectation is rationally unfounded, the brain does, making it more difficult to respond to task A when it occurs unexpectedly. As found in the findings from the studies on oddball (i.e., unexpected items), both the frontal and occipital lobes of the brain were generally observed to be highly activated when unanticipated and rare stimuli were presented ( Brazdil et al, 2007 ; Hooi et al, 2018 ), which is overlapped with regions of brain activation found during deinhibition ( Dreher and Berman, 2002 ; Picazio et al, 2020 ; Sdoia et al, 2020 ).…”
Section: Conceptual Definition and Theoretical Accountsmentioning
confidence: 80%
See 2 more Smart Citations
“…Interestingly enough, a recent study applied crosshemispheric tDCS over the prefrontal and parietal cortex, and showed that task switching performance increased only when it was required to overcome a previous inhibition in order to switch back to a recently inhibited task (Sdoia, Zivi, & Ferlazzo, 2020). As task switching depends on an extensive brain network, it is not surprising to consider that specific regions may be also responsible for specific functions that underlie the general cognitive ability.…”
Section: Discussionmentioning
confidence: 99%